2012
DOI: 10.1063/1.4761894
|View full text |Cite
|
Sign up to set email alerts
|

Rate coefficients from quantum and quasi-classical cumulative reaction probabilities for the S(1D) + H2 reaction

Abstract: Cumulative reaction probabilities (CRPs) at various total angular momenta have been calculated for the barrierless reaction S( 1 D) + H 2 → SH + H at total energies up to 1.2 eV using three different theoretical approaches: time-independent quantum mechanics (QM), quasiclassical trajectories (QCT), and statistical quasiclassical trajectories ( The results show that the differences between these two PES are relatively minor and mostly related to the different topologies of the well. In addition, the agreement b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…[4][5][6] Since that time, it was observed that the energy-dependence of quantum reaction probabilities involve sharp fluctuations whose amplitudes tend to decrease as the energy increases. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the present work, we have proposed a statistical analysis of these fluctuations based in part on classical S-matrix theory, [39][40][41][42] and in part on a few assumptions, the main ones being a chaotic classical dynamics and the validity of MPPST 35 them to the benchmark H + + H 2 reaction. 14 In conclusion, we believe that the statistical tools proposed in this paper should help analyzing future quantum scattering calculations on complex-forming chemical reactions and related processes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4][5][6] Since that time, it was observed that the energy-dependence of quantum reaction probabilities involve sharp fluctuations whose amplitudes tend to decrease as the energy increases. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In the present work, we have proposed a statistical analysis of these fluctuations based in part on classical S-matrix theory, [39][40][41][42] and in part on a few assumptions, the main ones being a chaotic classical dynamics and the validity of MPPST 35 them to the benchmark H + + H 2 reaction. 14 In conclusion, we believe that the statistical tools proposed in this paper should help analyzing future quantum scattering calculations on complex-forming chemical reactions and related processes.…”
Section: Discussionmentioning
confidence: 99%
“…7,28 Since then, many studies have confirmed the previous observations. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] The origin of the sharp fluctuations is rather well understood. The study of Smith life-time matrix 6,29,30 indeed reveals that fluctuations are resonance structures due to dense sets of metastable states above the dissociation limit of the intermediate complex.…”
Section: Introductionmentioning
confidence: 99%
“…Different TDWP approaches have been applied to study the S( 1 D)+H 2 [178][179][180][181], the S( 1 D)+D 2 [182] and the S( 1 D)+HD reactions [183,184] on various PESs [168,181,185,186]. Analogously, since the early work by Honvault and Launay [187] to reproduce both DCS and PTE distributions from Lee and Liu's measurements, other TIQM calculations have been reported [17,[174][175][176][177][188][189][190][191][192].…”
Section: S( 1 D)+hmentioning
confidence: 99%
“…The S( 1 D) + H 2 (X 1 Σ g + ) → H( 2 S) + SH(X 2 Π) reactive system and its isotopic variants have been studied both experimentally1234567 and theoretically891011121314151617181920212223242526. Several experimental studies have been performed to accurately describe the equilibrium geometry and a local potential energy surface123.…”
mentioning
confidence: 99%
“…The influence of the barrier on the DMBE/CBS PES at low energies was investigated9 in detail through a comparion with the results obtained on the Ho PES, and the two dynamical behaviors were very different. Jambrina et al 22 calculated the cumulative reaction probabilities of the title reaction using three different theoretical approaches: time-independent QM, QCT and statistical QCT. The agreement among the three methods was good indicating that the title reaction can be considered statistical.…”
mentioning
confidence: 99%